PENGARUH KESADARAN BERPOLITIK TERHADAP PARTISIPASI POLITIK KAUM MILLENIAL - Vera Wijayanti Sutjipto; Maulina Larasati Putri; Marisa Puspita Sary; Angieta Dewati Putri; Helyana Wulandari; Hasna Nur Fauziyah (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
Political awareness has an important role as one of the basic needs in forming one's political views. The influence and political direction of the millennial generation in democratic life can be shown from three factors, including: (1) potential for political participation and choice beliefs, (2) sensitivity to social issues and policies, and (3) inclination towards candidates and political choices. This study uses a descriptive quantitative method which has the aim of explaining and summarizing various conditions regarding political awareness among millennials. The population of this study is millennials aged 18 to 22 years who live in Greater Jakarta. The research data was collected by questionnaire from 100 respondents. The results of this study indicate that there is a significant influence between political awareness on political participation. The interest in political developments in Indonesia indicates that slowly the millennial generation is starting to realize the magnitude of the changes that politics will bring.